2015
DOI: 10.1039/c5dt00753d
|View full text |Cite
|
Sign up to set email alerts
|

A novel cobalt sodium phosphate hydroxide with the ellenbergerite topology: crystal structure and physical properties

Abstract: The novel phase Na2-xCo6(OH)3[HPO4][Hx/3PO4]3 (x≈ 1.1) was prepared by hydrothermal synthesis at 553 K. Its crystal structure was determined using single-crystal X-ray diffraction data and refined against F(2) to R = 0.052, including positions of all hydrogen atoms. The compound crystallizes in the hexagonal space group P63mc, with unit-cell parameters a = 12.630(3) Å, c = 5.017(1) Å, V = 693.1(3) Å(3), and Z = 2. The crystal structure is based on a 3D framework built from CoO6 octahedra and PO4 tetrahedra. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…To our knowledge, besides Na 2 Co 2 (C 2 O 4 ) 3 (H 2 O) 2 , the available examples are Co(C 8 H 8 O 4 ), Co 3 (2,5- pydc ) 2 ( μ 3 -OH) 2 (OH 2 ) 2 ( pydc  = pyridinedicarboxylate), Co 7 V 4 O 16 (OH) 2 (H 2 O) and Na 2− x Co 6 (OH) 3 [HPO 4 ][H x /3 PO 4 ] 3 111213. The properties of Co(C 8 H 8 O 4 ) have not been measured, while the rest of them exhibit an antiferromagnetic ordering far below room temperature.…”
mentioning
confidence: 99%
“…To our knowledge, besides Na 2 Co 2 (C 2 O 4 ) 3 (H 2 O) 2 , the available examples are Co(C 8 H 8 O 4 ), Co 3 (2,5- pydc ) 2 ( μ 3 -OH) 2 (OH 2 ) 2 ( pydc  = pyridinedicarboxylate), Co 7 V 4 O 16 (OH) 2 (H 2 O) and Na 2− x Co 6 (OH) 3 [HPO 4 ][H x /3 PO 4 ] 3 111213. The properties of Co(C 8 H 8 O 4 ) have not been measured, while the rest of them exhibit an antiferromagnetic ordering far below room temperature.…”
mentioning
confidence: 99%
“…The system of hydrogen bonds in I was analyzed on the basis of X-ray diffraction data obtained at a temperature of 50 K. The scheme of hydrogen bonding in I is slightly different from the scheme observed in Co phosphate . The O4–H1 group plays the role of a donor by forming bifurcated hydrogen bonds with the O6 and O3 oxygen atoms (Figure ), while in the crystal structure of the Co analog the corresponding O6–H1 group forms a hydrogen bond only with one O5 atom, strengthening the cationic framework.…”
Section: Resultsmentioning
confidence: 99%
“…The second fragment is a defective chain of face-sharing octahedra in the framework cavities with a hexagonal shape. These octahedra can also be centered by alkali metal cations, such as in the crystal structure of Na 2– x Co 6 (OH) 3 [HPO 4 ]­[H x /3 PO 4 ] 3 ( x ≈ 1.1) . Co-containing phosphates, vanadates, and arsenates of the ellenbergerite type were obtained as single-crystal phases and were thoroughly studied structurally.…”
Section: Introductionmentioning
confidence: 99%
“…According to ref , superexchange interactions between ferromagnetically coupled dimers of CoO 6 octahedra are responsible for the overall ferromagnetic character of the compound. Magnetic susceptibility measurements revealed a strong antiferromagnetic interaction and magnetic transition to low-temperature spin-canted phase at T N = 44 K for the Na 2– x Co 6 (OH) 3 [HPO 4 ]­[H x /3 PO 4 ] 3 ( x ≈ 1.1) with the ellenbergerite crystal structure . Recent discoveries have shown that nanoparticles of cobalt phosphates Co 3 (PO 4 ) 2 ·8H 2 O and Co 3 (PO 4 ) 2 are able to counteract Acanthamoeba and thus can be the basis for nanopreparations against these opportunistic microorganisms, carriers of infections that are dangerous to the eyes and cause fatal brain diseases …”
Section: Introductionmentioning
confidence: 99%